Nerve and Muscle / [electronic resource] - Keynes, Richard D.; Aidley, David J.; Huang, Christopher L.-H. (Cambridge : Cambridge University Press, 2011)
Written with undergraduate students in mind, the new edition of this classic textbook provides a compact introduction to the physiology of nerve and muscle. It gives a straightforward account of the fundamentals accompanied by some of the experimental evidence upon which this understanding is based. It first explores the nature of nerve impulses, clarifying their mechanisms in terms of ion flow through molecular channels in cell membranes. There then follows an account of the synaptic transmission processes by which one excitable cell influences activity in another. Finally, the emphasis turns to the consequences of excitable activity in the activation of contraction in skeletal, cardiac and smooth muscle, highlighting the relationships between cellular structure and function. This fourth edition includes new material on the molecular nature of ion channels, the activation of skeletal muscle and the function of cardiac and smooth muscle, reflecting exciting new developments in these rapidly growing fields.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Myoneural junction; Neuromuscular transmission; Muscle contraction